Alterações estruturais envolvendo o cromossomo x: impacto da inativação preferencial no fenótipo dos pacientes - Battista, Adriana Di [UNIFESP] (2016)
X-chromosome rearrangements are usually associated with distinct X inactivation patterns, which can influence in patient?s phenotype. To better understand the mechanisms involved in cell selection and the clinical consequences in these cases, it?s important to characterize the rearrangement structures and determine the inactivation pattern, as well as the morphology of the X-chromosome preferentially inactivated. Patient 1, carrier of a de novo balanced translocation t(X;19)(p21.1;q13.4), presents with moderate intellectual disability. Disrupted genes in both chromosomes lead to formation of chimeric genes. Patient 2 carries a derivative chromosome inherited from his mother, which carries a balanced translocation t(X;15)(q10;p13). He presents with severe intellectual disability and epilepsy. In this patient, the X-chromosome portion of the derivative chromosome is preferentially inactivated and is possible that a spread of inactivation to chromosome 15 could be causing his phenotype. Patients 3 and 4 are, respectively, mother and daughter and carriers of the same altered X-chromosome, formed from a partial Xp deletion and partial Xq duplication. In patient 4, this chromosome is supranumerary. It is possible that their phenotypic differences are due to genic dosage imbalance in regions that escape X inactivation. Patient 5 carries a 9,7 Mb interstitial microduplication involving Xp11.3-Xp11.22. Unexpectedly, the normal X-chromosome is preferentially inactivated, resulting in increased expression of the duplicated genes and leading to a severe phenotype. It it possible that some genes from the duplicated region, related to cell-cycle control and cell division, favors the aberrant X-chromosome, acting as a selective factor on dividing cells.